Prevalence and risk factors of intestinal parasitism in rural and remote west Malaysia - Ngui, R.; Ishak, S.; Chuen, C. S.; Mahmud, R.; Lim, Y. A. L. (Public Library of Science, 2011)
Background: Intestinal parasitic infections (IPIs) have a worldwide distribution and have been identified as one of the most significant causes of illnesses and diseases among the disadvantaged population. In Malaysia, IPIs still persist in some rural areas, and this study was conducted to determine the current epidemiological status and to identify risk factors associated with IPIs among communities residing in rural and remote areas of West Malaysia. Methods/Findings: A total of 716 participants from 8 villages were involved, comprising those from 1 to 83 years old, 550 (76.8) participants aged <= 12 years and 166 (23.2) aged >= 13 years, and 304 (42.5) male and 412 (57.5) female. The overall prevalence of IPIs was high (73.2). Soil-transmitted helminth (STH) infections (73.2) were significantly more common compared to protozoa infections (21.4) (p<0.001). The prevalence of IPIs showed an age dependency relationship, with significantly higher rates observed among those aged <= 12 years. Multivariate analysis demonstrated that participants aged <= 12 years (OR = 2.23; 95 CI = 1.45-3.45), low household income (OR = 4.93; 95 CI = 3.15-7.73), using untreated water supply (OR = 2.08; 95 CI = 1.36-3.21), and indiscriminate defecation (OR = 5.01; 95 CI = 3.30-7.62) were identified as significant predictors of IPIs among these communities. Conclusion: Essentially, these findings highlighted that IPIs are highly prevalent among the poor rural communities in West Malaysia. Poverty and low socioeconomic with poor environmental sanitation were indicated as important predictors of IPIs. Effective poverty reduction programmes, promotion of deworming, and mass campaigns to heighten awareness on health and hygiene are urgently needed to reduce IPIs.